2020
DOI: 10.3390/ijerph18010144
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Exposure to Fine Particulate Matter and Hospitalizations for Acute Lower Respiratory Infection in Korean Children: A Time-Series Study in Seven Metropolitan Cities

Abstract: Although several studies have evaluated the association between fine particulate matter (PM2.5) and acute lower respiratory infection (ALRI) in children, their results were inconsistent Therefore, we aimed to evaluate the association between short-term exposure to PM2.5 and ALRI hospitalizations in children (0–5 years) living in seven metropolitan cities of Korea. The ALRI hospitalization data of children living in seven metropolitan cities of Korea from 2008 to 2016 was acquired from a customized database con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…In this study, LRTI encounters for children increased with elevated PM2.5 and peaked at a weekly average lag of 6–12 days Studies on this category of respiratory infections or specific infections within this category (e.g., bronchitis or pneumonia) vary in their findings. To discuss a few, numbers of acute lower respiratory infections for young children in Utah, USA, were found to increase after 1 week of increased PM 2.5 and peak after 3 weeks of an increased exposure ( Horne et al 2018 ), while a similar study and results from Korea found acute lower respiratory infection hospitalizations to be associated with an increase in the 7-day running average of PM 2.5 ( Oh et al 2021 ). Zhu et al (2017) did not find a significant effect of short-term PM 2.5 on childhood lower respiratory diseases in China, but did observe the effect with other air pollutants (PM 10 , NO 2 , and SO 2 ).…”
Section: Discussionmentioning
confidence: 98%
“…In this study, LRTI encounters for children increased with elevated PM2.5 and peaked at a weekly average lag of 6–12 days Studies on this category of respiratory infections or specific infections within this category (e.g., bronchitis or pneumonia) vary in their findings. To discuss a few, numbers of acute lower respiratory infections for young children in Utah, USA, were found to increase after 1 week of increased PM 2.5 and peak after 3 weeks of an increased exposure ( Horne et al 2018 ), while a similar study and results from Korea found acute lower respiratory infection hospitalizations to be associated with an increase in the 7-day running average of PM 2.5 ( Oh et al 2021 ). Zhu et al (2017) did not find a significant effect of short-term PM 2.5 on childhood lower respiratory diseases in China, but did observe the effect with other air pollutants (PM 10 , NO 2 , and SO 2 ).…”
Section: Discussionmentioning
confidence: 98%
“…Studies on this category of respiratory infections or specific infections within this category (e.g., bronchitis or pneumonia) vary in their findings. To discuss a few, numbers of acute lower respiratory infections for young children in Utah, USA, were found to increase after 1 week of increased PM 2.5 and peak after 3 weeks of an increased exposure [ 35 ], while a similar study and results from Korea found acute lower respiratory infection hospitalizations to be associated with an increase in the 7-day running average of PM 2.5 [ 66 ]. Zhu et al [ 99 ] did not find a significant effect of short-term PM 2.5 on childhood lower respiratory diseases in China, but did observe the effect with other air pollutants (PM 10 , NO 2 , and SO 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies from several regions, including Taiwan and Jinan in China, found that elevated particulate matter concentrations were associated with increased outpatient visits and hospitalizations for pneumonia [ 29 , 30 ]. A study conducted in South Korea revealed that the concentration of PM 2.5 at lag06 caused the greatest risk of ALRI hospitalization in children [ 12 ]. In a case-crossover study of 112,467 children in the U.S., 1-week exposure to PM 2.5 was found to be associated with hospitalization for ALRI in children aged 0–2 years and 3–17 years [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Children are particularly vulnerable to air pollution because their lung immune system is still developing. A number of studies conducted in different countries have demonstrated an association between long-term or short-term exposure to air pollutants and childhood ALRI hospitalization [10][11][12][13]. There are also several studies from China that have focused on the effects of air pollutants on the hospitalization of children with ALRI.…”
Section: Introductionmentioning
confidence: 99%